Mathematics teacher education: Sharing experiences and mathematical knowledge (Revista Contexto & Educação, 2023)
This article explores reflections on mathematical knowledge and the exchange of experiences among Mathematics teachers participating in a continuing formation in Mathematical Modeling in Mathematics Education. These reflections are based on the interpretation of the data of the research, constituted from the transcription of the audios of 14 training meetings and the testimony of 10 participants. The research, conducted in the phenomenological-hermeneutic attitude, sought to contribute to the area of teacher training in Mathematical Modeling, showing how Mathematics teachers understand mathematical knowledge and how to exchange experiences between peers. We understand that the pedagogical changes, on the part of those who teach Mathematics, do not occur immediately and solitary. Thus, a formative model that values the teacher's experience and that articulates the difficulties of the school context he experiences favors the motivation for participation in the formation and the change of practice.
Keywords: Mathematical Modeling. Professional Experiences. Mathematics Teaching. Training Model.